Toll-like receptor 2 (−196 to −174) del and TLR1 743 A > G gene polymorphism—a possible association with drug-resistant tuberculosis in the north Indian population - Varshney, Deepika; Singh, Shoor Vir; Mohanty, Keshar Kunja; Kumar, Santosh; Varshney, Nitin; Sinha, Ekata; Barik, Sushanta Kumar (Frontiers in Microbiology, 2024)
Objectives The objective of this study is to analyze the association between TLR2 deletion (−196 to −174) and TLR1 743 A > G gene polymorphism with drug resistant tuberculosis (PTB, MDR-TB, and XDR-TB) in a population from Agra, Uttar Pradesh. Methods The present case–control study included 101 pulmonary TB patients, 104 multidrug-resistant TB patients, 48 extremely drug-resistant TB patients, and 130 healthy and unrelated controls residing in the same locality. The genotyping method for TLR2 deletion (−196 to −174) was carried out by allele-specific polymerase chain reaction (PCR), and TLR1 743 A > G gene polymorphism was performed by hybridization probe chemistry in Roche Real-Time PCR. Genotype and allele frequencies were analyzed by the chi-square test. Cytokine levels were measured by ELISA and compared using Mann–Whitney and Kruskal–Wallis tests. Results The frequency of heterozygous (Ins/del) genotypes for TLR2 (−196 to −174) polymorphism was predominant in XDR-TB patients (0.57), whereas heterozygous A/G genotype for TLR1 743 A > G single nucleotide polymorphism (SNP) was predominant in healthy controls (0.57) for TLR1 743 A > G gene polymorphism. The heterozygous genotype of TLR2 deletion polymorphism was found to be significantly higher in XDR-TB (p = 0.0001). TLR1 743 A > G SNP, AG genotypes were found to be significantly associated with healthy controls than PTB (p = 0.047). The level of serum cytokines (IL-6, TNF-α, and IFN-γ) was also found to be significantly different among TB patients and healthy controls. Conclusion The findings suggested that in the present population, the heterozygous (Ins/Del) genotype and deletion allele of TLR2 deletion (−196 to −174) polymorphism are associated with the risk for the development of drug-resistant TB. Furthermore, for TLR1 743 A > G gene polymorphism, A/G genotype, and G allele are found associated with healthy controls, suggesting the protective role against TB.